The Network of Online Stolen Data Markets: How Vendor Flows Connect Digital Marketplaces - Ouellet, Marie (The British journal of criminology, 2022)
In the face of market uncertainty, illicit actors on the darkweb mitigate risk by displacing their operations across digital marketplaces. In this study, we reconstruct market networks created by vendor displacement to examine how digital marketplaces are connected on the darkweb and identify the properties that drive vendor flows before and after a law enforcement disruption. Findings show that vendors’ movement across digital marketplaces creates a highly connected ecosystem; nearly all markets are directly or indirectly connected. These network characteristics remain stable following a law enforcement operation; prior vendor flows predict vendor movement before and after the interdiction. The findings inform work on collective patterns in offender decision-making and extend discussions of displacement into digital spaces.